2017
DOI: 10.1016/j.tox.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl acids-induced liver steatosis: Effects on genes controlling lipid homeostasis

Abstract: Persistent presence of perfluoroalkyl acids (PFAAs) in the environment is due to their extensive use in industrial and consumer products, and their slow decay. Biochemical tests in rodent demonstrated that these chemicals are potent modifiers of lipid metabolism and cause hepatocellular steatosis. However, the molecular mechanism of PFAAs interference with lipid metabolism remains to be elucidated. Currently, two major hypotheses are that PFAAs interfere with mitochondrial beta-oxidation of fatty acids and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
149
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(168 citation statements)
references
References 77 publications
17
149
2
Order By: Relevance
“…Hepatic lipid accumulation has also been reported in mice upon exposure to perfluoroalkyl acids ( Das et al. 2017 ), perfluorooctanoic acid ( Hui et al.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hepatic lipid accumulation has also been reported in mice upon exposure to perfluoroalkyl acids ( Das et al. 2017 ), perfluorooctanoic acid ( Hui et al.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, pesticide exposure led not only to steatosis glucose intolerance and elevated blood glucose, but also resulted in greater WAT mass and BW and more circulating FFAs in WT male mice compared to unexposed WT male mice. Previous studies showed that steatosis induced in mice by perfluoroalkyl acids ( Das et al. 2017 ) and perfluorooctanoic acid ( Yan et al.…”
Section: Discussionmentioning
confidence: 99%
“…In rats and mice treated with APFO, liver effects such as increased serum ALT and AST values ( Butenhoff et al , 2012a ; Minata et al , 2010 ; Son et al , 2008 ); peroxisome proliferation with subsequent hepatocellular hypertrophy ( Elcombe et al , 2010 ; Haughom and Spydevold, 1992 ; Loveless et al , 2006 ;); and increased incidence of hepatocellular adenoma in rats ( Biegel et al , 2001 ; Butenhoff et al , 2012a ) were reported, but these changes were attributed to PPARα activation, a mode of action unlikely to result in human liver tumors ( Corton et al , 2014 ; Das et al , 2017 ). An increased liver weight reported in an APFO feeding study of monkeys was due, in part, to adaptive hepatocellular hypertrophy possibly as a result of mitochondrial proliferation ( Butenhoff et al , 2002 ); no corroborative changes in either serum ALT or alkaline phosphatase occurred.…”
Section: Discussionmentioning
confidence: 99%
“…There are concerns about the human health impacts of some PFASs, particularly PFOA, PFOS, and other perfluoroalkyl substances. Briefly, in rodent studies, these compounds are known to affect lipid metabolism (e.g., Das et al. 2017 ) and liver weight (e.g., Loveless et al.…”
Section: Introductionmentioning
confidence: 99%